Pengaruh Pengalaman, Independensi, Keahlian dan Skeptisme Profesional Auditor terhadap Pendeteksian Kecurangan (Studi Kasus pada Badan Pemeriksa Keuangan RI Perwakilan Provinsi Kalimantan Timur) - Hasnawiah Hasnawiah (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
This study aims to determine the influence of independence, expertise and skepticism of auditor professionals to the detection of fraud at the State Audit Board of the Republic of Indonesia Representative of East Kalimantan. Data collection was done by giving 49 questionnaires, but only 27 questionnaires could be analyzed and processed. Questionnaires were distributed to respondents who worked as auditors at the State Audit Board of the Republic of Indonesia Representative of East Kalimantan. The data obtained is then analyzed using SmartPLS. The results showed that Independence and Expertise have no significant effect on Fraud Detection, and Professional Skepticism of Auditor has no significant effect on Fraud Detection.Keywords: Independence, Expertise, Professional Skepticism Auditor and Fraud Detection